Comparative evaluation of cDNA library construction approaches for RNA-Seq analysis from low RNA-content human specimens - Masters, T.L.; Hilker, C.A.; Jeraldo, P.R.; Bhagwate, A.V.; Greenwood-Quaintance, K.E.; Eckloff, B.W.; Chia, N.; Hanssen, A.D.; Abdel, M.P.; Yao, J.Z.; Jen, J.; Patel, R. (Journal of microbiological methods, 2018)
With the emergence of RNA sequencing technologies, metatranscriptomic studies are rapidly gaining attention as they simultaneously provide insight into gene expression profiles and therefore disease association pathways of microbial pathogens and their hosts. This approach, therefore, holds promise for applicability in infectious disease diagnostics. A challenge of this approach in the clinical setting is the low amount and quality of RNA, especially microbial RNA in most clinically-infected specimens. Here, we compared two commercially available stranded cDNA library preparation kits, the NuGEN Ovation SoLo RNA-Seq System and the Illumina TruSeq Stranded Total RNA, using RNA extracted from synovial and sonicate fluids from a subject with periprosthetic joint infection. The Ovation SoLo RNA-Seq System provided more useful transcriptomic data for the infecting bacterium, whereas the TruSeq Stranded Total RNA kit provided more useful human transcriptomic data. •Compared 2 cDNA library kits for human samples undergoing transcriptomic analysis•The Ovation SoLo RNA-Seq System was superior for bacterial transcriptomic analysis.•The TruSeq Stranded Total RNA kit did better for human transcriptomic analysis.